Impact Of Culture Conditions On The Production Of Curvacin A By Lactobacillus Curvatus Lc05 - A.MOHAN KUMAR,; S.ARUMUGAM, (International Journal of Pharma and Bio Sciences, 2012)
Curvacin A, a type of bacteriocin produced by Lactobacillus curvatus LC05 has large spectrum of inhibition against human pathogenic, food spoilage microorganisms and many strains of Lactobacillus were isolated as a test organisms. The Curvacin A inhibited Enterococcus faecalis EF1 Escherichia coli NCTC 10418 but did not inhibit Candida albicans ATCC 10321. The antibacterial activity of the strains were observed between mid lograthmic and stationary phase of growth. Larger quantity of Curvacin A was found produced when the medium is supplemented with yeast extract (3.0%) sodium chloride (1.0-2.0%), glucose (1%) and Tween 80 (0.5%). Supplementation of sodium acetate, magnesium sulphate, tri ammonium citrate and dipotassium phosphate had no effect on production of Curvacin A.